Weed Control in Okra - William M. Stall (EDIS)
Revised! HS-192, a 2-page fact sheet by William M. Stall, describes effective weed management practices for okra in Florida and provides a table of listing herbicides available to growers for chemical weed control. This publication updates the 2003 tables to reflect current recommendations. Published by the UF Department of Horticultural Sciences, October 2006.